Aberrant angiogenic signaling in HCC: therapeutic targeting and drug resistance - Zhang, Hongtao; Yang, Zhaoming; Jiang, Zhengwu; Zhao, Zhijian; Chen, Xun; Wan, Jian; Li, Yukun (Frontiers in Oncology, 2025)
Liver cancer ranks as the sixth most prevalent malignancy globally, with Hepatocellular Carcinoma (HCC) constituting the predominant subtype, thereby imposing a significant burden on public health and presenting limited therapeutic options. Despite ongoing efforts to innovate treatment modalities, anti-angiogenesis therapy continues to be the primary strategy for managing HCC. Angiogenesis is a pivotal process within the tumor microenvironment, characterized by the formation of new blood vessels that provide essential nutrients and oxygen to proliferating tumors, thereby facilitating their growth and potential metastasis. Numerous angiogenic signaling pathways become dysregulated during this process. Targeting these aberrant pathways can yield significant therapeutic benefits for patients and may even reverse drug resistance. However, these signaling pathways frequently demonstrate intricate crosstalk and interconnections. Elucidating these interactions could represent a crucial strategy for advancing the treatment of HCC. This review provides both mechanistic insights into angiogenic network plasticity and translational strategies to overcome therapeutic bottlenecks in HCC management.